1998
DOI: 10.1175/1520-0493(1998)126<0913:tpfatt>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Tibetan Plateau Forcing and the Timing of the Monsoon Onset over South Asia and the South China Sea

Abstract: Observations were employed to study the thermal characteristics of the Tibetan Plateau and its neighboring regions, and their impacts on the onset of the Asian monsoon in 1989. Special attention was paid to the diagnosis of the temporal and spatial distributions of surface sensible and latent heat fluxes. Results show that the whole procedure of the outbreak of the Asian monsoon onset is composed of three consequential stages. The first is the monsoon onset over the eastern coast of the Bay of Bengal (BOB) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
387
0
8

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 545 publications
(401 citation statements)
references
References 32 publications
6
387
0
8
Order By: Relevance
“…For the late season, correlation coefficients are yet higher, and the band of high correlation extends southwest from Tibet. These correlations suggest a direct relationship between heating of the atmosphere directly above Tibet's surface, and the temperature in the upper troposphere, which many link both to the strength of the monsoon [e.g., Goswami et al, 1999;He et al, 1987He et al, , 2003Li and Yanai, 1996;Wu and Zhang, 1998;Yanai and Wu, 2006;Yanai et al, 1992] and, as Chakraborty et al [2006] suggested, to its onset [e.g., Goswami and Xavier, 2005;Xavier et al, 2007;Webster and Yang, 1992].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the late season, correlation coefficients are yet higher, and the band of high correlation extends southwest from Tibet. These correlations suggest a direct relationship between heating of the atmosphere directly above Tibet's surface, and the temperature in the upper troposphere, which many link both to the strength of the monsoon [e.g., Goswami et al, 1999;He et al, 1987He et al, , 2003Li and Yanai, 1996;Wu and Zhang, 1998;Yanai and Wu, 2006;Yanai et al, 1992] and, as Chakraborty et al [2006] suggested, to its onset [e.g., Goswami and Xavier, 2005;Xavier et al, 2007;Webster and Yang, 1992].…”
Section: Resultsmentioning
confidence: 99%
“…Rather the monsoon begins abruptly in a period as short as two weeks, as measured not only by precipitation [e.g., Soman, 1988, 1989;Joseph et al, 2006;Pai and Nair, 2009;Soman and Krishna Kumar, 1993], but also by reversals in both low-level winds [e.g., Boos and Emanuel, 2009;Fieux and Stommel, 1977;Halpern and Woiceshyn, 1999;Krishnamurti et al, 1981] and upper troposphere circulation [e.g., He et al, 1987He et al, , 2003Li and Yanai, 1996;Wu and Zhang, 1998;Yanai and Wu, 2006;Yanai et al, 1992]. Moreover, Goswami et al [1999] showed that the reversal in winds aloft correlates with onsets of monsoons defined by various rainfall indices.…”
Section: Introductionmentioning
confidence: 99%
“…3). During summer, low pressure over the surface of the plateau (Tibetan Low) induces a supply of moist and warm air from the Indian Ocean to the continent (summer monsoon), meanwhile, in the upper troposphere the Southern Asian High centers over the Tibetan Plateau and drives air mass moving out of the plateau (Wu and Zhang, 1998;Li, 2002). Then, there is South Asian Monsoon Cell (inverse to the Hadley Cell) formed between the Tibetan Plateau and the Indian Ocean, which transports moisture into the Tibetan Plateau from Indian Ocean in the lower troposphere and sends air back in the upper troposphere (Zhou, 1997;Li, 2002).…”
Section: Seasonality Of Concentrations Of Culturable Bacteriamentioning
confidence: 99%
“…Based on diverse datasets and methods, many results showed that the initial onset of the ASM occurs in the eastern Bay of Bengal (BOB) and ICP in the second to third pentad of May on average (e.g. Wang, 1994;He et al, 1996;Webster et al, 1998;Wu and Zhang, 1998;Qian and Yang, 2000;Wang and LinHo, 2002;Zhang et al, 2002), which is somewhat earlier than that of the SCS summer monsoon.…”
Section: Introductionmentioning
confidence: 99%
“…So far, the mechanism of the convection onset has not been comprehended entirely, and its relationship with the tropical convection deserves further investigation. The roles of the propagation of the Low-frequency Oscillation (LFO) and the phase-lock of LFOs with different periods in the onset of the ICP summer monsoon have been emphasized by Wu and Zhang (1998) and Zhang et al (2002), especially the quasi-biweekly oscillation (QBWO). One of the purposes of this study is to investigate whether the QBWO exerts the same important effect on the onset of the ICP convection.…”
Section: Introductionmentioning
confidence: 99%